Methylfarnesoate Enhances Growth in Macrobrachium rosenbergii - Neethu. M; Kiran Dube; V.K Tiwari; Nalini Poojary (Journal of Indian Fisheries Association, 2019)
Eﬀect of exogenous methylfarnesoate supplementation on molting of freshwater prawn Macrobrachium rosenbergii was studied with diﬀerent doses of methylfarnesoate (0.25, 0.5, 0.75, 1.00 and 1.25ᶙg of MF/20g prawn). The prawns which didn’t receive any injection were served as control while the prawns which got an injection of distilled water were regarded as concurrent control. Female prawns of 30±2g and male prawns of 45±2g were reared separately in triplicates for 60 days duration. Growth parameters were recorded at an interval of 10 days along with molting frequency, and inter-molt period. The results revealed that the groups which were injected with 1.25ᶙg of methylfarnesoate per 20 g of prawn attain highest growth, highest length increment with lowest molting frequency. The longest intermolt period was 32 and 28 days for male and female prawns respectively recorded was for the concurrent control, while the shortest period (12 and 11.6 days for male and female prawns respectively) was for the highest dose injected prawns. These results revealed that methylfarnesoate supplementation at high dose (1.25ᶙg MF/20g) could significantly increase the growth performance of freshwater prawn independent of the sex.